Exposure levels, determinants and risk assessment of organophosphate flame retardants and plasticizers in adolescents (14–15 years) from the Flemish Environment and Health Study. (February 2021) - Bastiaensen, Michiel; Gys, Celine; Colles, Ann; Verheyen, Veerle; Koppen, Gudrun; Govarts, Eva; Bruckers, Liesbeth; Morrens, Bert; Loots, Ilse; De Decker, Annelies; Nelen, Vera; Nawrot, Tim; et al.
Highlights: First large-scale study on exposure to PFRs in an European population. Six metabolites of 7 PFRs were frequently detected in Flemish adolescents. Relatively high exposure to EHDPHP as confirmed by two urinary metabolites. Socio-economic status and building materials were determinants of exposure. Estimated daily intakes were all below oral reference doses (RfD) Abstract: The ubiquitous use of organophosphate flame retardants and plasticizers (PFRs) in a variety of consumer products has led to widespread human exposure. Since certain PFRs are developmental and carcinogenic toxicants, detailed exposure assessments are essential to investigate the risk associated with environmental exposure levels. However, such data are still lacking for European countries. In this study, concentrations of thirteen PFR metabolites were measured in urine samples from 600 adolescents from Flanders, Belgium. 1-Hydroxy-2-propyl bis(1-chloro-2-propyl) phosphate (BCIPHIPP), diphenyl phosphate (DPHP), bis(1, 3-dichloro-isopropyl) phosphate (BDCIPP), 2-hydroxyethyl bis(2-butoxyethyl) phosphate (BBOEHEP), 2-ethylhexyl phenyl phosphate (EHPHP) and 2-ethyl-5-hydroxyhexyl diphenyl phosphate (5-HO-EHDPHP) were frequently detected (>83%) in all participants. Comparisons with study populations from outside the EU showed that urinary levels of DPHP, BDCIPP and BCIPHIPP were generally within the same range. Only exposure to 2-ethylhexyl diphenyl phosphate (EHDPHP) was presumably higher in Flemish adolescents. However, determinants analysis through multivariate regression analyses did not reveal significant predictors that may explain this finding. Significantly higher levels of BDCIPP were observed in participants with new decorations at home, while adolescents with highly educated parents had higher levels of BBOEHEP and BDCIPP. Furthermore, multiple PFR metabolite concentrations followed a seasonal pattern. Estimated daily intakes (EDIs) were calculated from the internal dose by including fractions of urinary excretion (FUE ) estimated in in vitro metabolism studies. EDIs ranged from 6.3 ng/kg bw/day for TBOEP to 567.7 ng/kg bw/day for EHDPHP, which were well below the available oral reference doses for all investigated PFRs. This suggests that the associated risk is low at present. This is the first report on internal exposure to seven commonly used PFRs in a European population.